Pengaruh Promosi Dan Harga Terhadap Keputusan Pembelian Pada PT. Wahana Chemindo Jaya Medan - Sarah, Eva Margareth; Tumanggor, Wennita (Metta : Jurnal Ilmu Multidisiplin, 2021)
The studi aims to determine whether promotions and prices have a significant effect on purchasing decisions at PT. Wahana Chemindo Jaya Medan. Where the consumers from PT. Wahana Chemindo Jaya Medan. The population in this study were all customers of PT. Wahana Chemindo Jaya Medan. The sample taken was 65 respondent using a non probability sampling technique. The data analysis method used is quantitative metdhod and data analysis method consisting of normality test, and heteroscedasticity test, multiple linaer regression terst, hypothesis testing consisting of t test and f test and coefficient od determination test (R2). Working on data analysis methods using the help os SPSS 25 For windows.This study concludes that the promotion and price variabel have a positive and significant impact on purchasing decions at PT. Wahana Chemindo Jaya Medan. This result can be seen based on the coefficient of determination test which produces an R square value of 0,787. This shows that promotions and prices are able to influence the purchasing decisions of customers of PT. Wahana Chemindo Jay Medan by 78,7%.